Bladder necrosis: 'A man without a bladder'. (17th February 2018) - Bosschieter, Judith; Oudshoorn, Frederik H K; Meuleman, Eric J H; Nieuwenhuijzen, Jakko A
Abstract : Since the use of antibiotics, bladder necrosis has become a rare condition. We report a case of bladder necrosis in a 90-year-old man following urinary retention. After insertion of a transurethral catheter (TUC), 2 L of urine was evacuated. In the following days, the TUC became intermittently blocked. Adequate bladder drainage could not be obtained despite intensive rinsing and placement of a suprapubic catheter. On surgical exploration necrosis of almost the entire bladder wall, except for the trigone, was encountered. Surgical debridement of the non-viable bladder wall without opening the abdominal cavity was conducted, and a TUC was placed in the Retzius cavity to ensure evacuation of urine. Since the patient was haemodynamically unstable, construction of a urinary diversion was waived and urinary drainage of the Retzius cavity by the TUC was accepted, resulting in adequate urinary drainage without compromising renal function.